Diskursus Rasm ‘Usmaniy dan Dinamika Naskah-Naskah Awal Qur’an Sebelum Abu Amr Ad-Daniy (W. 444/1053) - Muhammad, Wildan Imaduddin (Lajnah Pentashihan Mushaf Al-Qur'an, 2024)
This research attempts to open the intersection between the discourse surrounding Rasm ‘Usmaniy and the historical development of early Quranic manuscripts. This study focused on the impact of the belief in the Rasm ‘Usmaniy as the only valid writing model on the perception of the Quran’s originality. By comparing early Quranic manuscripts with the rules of the Rasm ‘Usmaniy, the research has revealed significant differences and similarities, contributing to a deeper understanding of the evolution of Quranic scripts. The findings have implications for the broader discourse on the authenticity of the Quran and the transmission of the Quranic text. This paper recommends further studies to explore the Rasm ‘Usmaniy discourse in different cultural and geographical contexts and to continue examining the differences in readings and the development of research on early Quranic manuscripts.